The Effectiveness of Animation Video Media on Learning Outcomes of Fiqih Lessons for Madrsah Ibtidaiyah Students in the New Normal Time - Alimni Alimni; Alfauzan Amin; Meri Lestari (Journal of Primary Education (JPE), 2021)
The purpose of this study is to see how animated video media affects student learning outcomes in memorizing the reading of the obligatory prayers in Fiqh subjects at MIN 2 Bengkulu. The type of research used is quantitative with an experimental approach. Based on the survey results, it can be concluded that there is effectiveness between the use of animated video media and without animated video media. This can be proven from the results of the "t" test. While t count = 2.673, then t table with df 38 at a significance level of 5% is 2.024. Thus, t arithmetic > t table (2.673 > 2.024) means that the working hypothesis (Ho) of this study is accepted. In other words, there are difference between the use of animated video media and without lively video media on the fiqh learning outcomes of second-grade students of MIN 2 Bengkulu city. This proves that the use of animated video media has improved student learning outcomes. Therefore, the average post-test result of Class II- A Fiqh training is higher than Class II B. That is, 80.45 after testing > 75.45 after testing. Accordingly, researchers suggest educators to apply animated video media to improve student learning outcomes, especially in Islamic law(fiqh) subjects.